Alleviation of salinity stress in wheat through silicon application - Tahir, Mukkram Ali; Noor-Us-Sabah; Sarwar, Ghulam; Moeez, Abdul; Latif, Muhammad (Journal of Pure and Applied Agriculture, 2023)
This research was performed to testify positive impact of silicon (Si) in alleviation of salinity and wheat growth and yield. Wheat variety Punjab-2011 was grown under normal and salt affected environments using Randomized Complete Block Design (RCBD) with three treatments and three replicates. Wheat was raised in plots filled with normal soil (EC = 2.32 dS/m) and salty soil (4.93 dS/m). Si as phosphate industry waste was applied @ 0, 50 and 100 µg Si/g soil. Results showed that application of Si reduces the adverse impact of salinity and significantly enhances the growth and yield of wheat plants under normal as well as salt stressed environments. Under salt affected soil environment, Si application at 100 µg Si/g (T3) resulted in maximum height of wheat plant (97 cm), spike length (13.27 cm), fertile tillers number per spike (5), grains count (39), 1000-grain weight (34.54 g), shoot fresh biomass (20.52 g), shoot dry matter (8.42 g), wheat grain yield (4.3 t/ha), silicon concentration in shoot (2.25 mg/g) and root (3.35 mg/g), total chlorophyll content (27 mg/g of fresh weight ) as well as total soluble protein content (93 mg/g dry matter). Likewise, under normal soil environment values for maximum height of wheat plant (100 cm), spike length (13.32 cm), fertile tillers (6), grains count (41), 1000-grain weight (35.22 g), shoot fresh biomass (25.65 g), shoot dry matter (10.12 g), wheat grain yield (5.5 t/ha), silicon concentration in shoot (2 mg/g) and in root (3.18 mg/g), total chlorophyll content (32 mg/g of fresh weight) as well as total soluble protein content (119.3 mg/g dry matter) were obtained with application of T3. Best results were obtained when maximum concentration of Si (100 µg Si/g) was applied. However, these results required to be testified using different wheat varieties under different salt concentrations in future. © 2021 Department of Agricultural Sciences, AIOU